Research progress on the anti-tumor effect of Naringin - He, Jing; Zhang, Hui-Ping (Frontiers in Pharmacology, 2023)
Naringin is a kind of natural dihydro flavone, which mainly exists in citrus fruits of the Rutaceae family, as well as traditional Chinese medicines such as trifoliate orange, fingered citron, exocarpium citri grandis, and rhizoma dynamite. Modern pharmacological studies have shown that Naringin has excellent anti-tumor activity. Through reviewing the relevant literature at home and abroad in recent years, we summarized the pharmacological mechanism of Naringin to play an anticancer role in blocking tumor cell cycle, inhibiting tumor cell proliferation, inducing tumor cell apoptosis, inhibiting tumor cell invasion and metastasis, inducing tumor cell autophagy, reversing tumor cell drug resistance and enhancing chemotherapeutic drug sensitivity, as well as anti-inflammatory to prevent canceration, alleviate Adverse drug reaction of chemotherapy, activate and strengthen immunity, It provides theoretical basis and reference basis for further exploring the anticancer potential of Naringin and its further development and utilization.